Effects of curcumin and yucca extract addition in feed of broilers on microorganism control (anticoccidial and antibacterial), health, performance and meat quality - Galli G.M.* (2020)
© 2020 Elsevier LtdThe aim of this study was to determine whether curcumin and yucca extract addition in broiler feed improves growth, health, and meat quality, and to measure coccidiostatic and antimicrobial activity so as to enable replacement of conventional performance enhancers. We used 240 birds in four treatments: CN, basal feed with antibiotics and coccidiostatic drugs; CU, feed with 100 mg/kg of curcumin; YE, feed with 250 mg/kg of yucca extract; and CU + YE, feed with the combination of 100 mg curcumin/kg and 250 mg yucca extract/kg. A significant reduction in oocysts was observed in birds supplemented with combined additives (CU + YE) at days 37 compared to other treatments and at 42 days in relation to the CU treatment. At 42 days, the total bacterial counts for the CN and CU treatments were lower than the others. Birds fed the additive had lower numbers of leukocytes, lymphocytes, and heterophils than did those in the CN treatment. The highest levels of antioxidants in meat were observed in the treatments with the additives, together with lower levels of lipid peroxidation compared to the CN. The lowest protein oxidation was observed in the CU + YE treatment in relation to the other treatments. Lower total levels of saturated fatty acids (SFA) were observed in the CU treatment than in the CN. There were lower levels of monounsaturated fatty acids (MUFA) in the meat of birds in the YE treatment in relation to the others. Higher levels of total polyunsaturated fatty acids (PUFA) were observed in birds that consumed curcumin, individually and in combination with yucca extract. Taken together, the data suggest that curcumin and yucca extract are additives that can potentially replace conventional growth promoters; they improved bird health. Changes in the fatty acid profile of meat (increase in the percentage of omegas) are beneficial to the health of the consumer.